It's about time; divergent circadian clocks in livers of mice and naked mole‐rats. Issue 5 (19th April 2021) - Ghosh, Soumyaditya; Lewis, Kaitlyn N.; Tulsian, Richa; Astafev, Artem A.; Buffenstein, Rochelle; Kondratov, Roman V.
Abstract: Light is the key regulator of circadian clock, the time‐keeping system synchronizing organism physiology and behavior with environmental day and night conditions. In its natural habitat, the strictly subterranean naked mole‐rat ( Heterocephalus glaber ) has lived in a light‐free environment for millennia. We questioned if this species retains a circadian clock and if the patterns of this clock and concomitant rhythms differed in liver tissue from mice and naked mole‐rats. As expected, in mice, the various circadian clock genes peaked at different times of the day; the Period gene ( Per ) group peaked in the evening, whereas Brain and Muscle ARNT‐like1 ( Bmal1 ) gene peaked in the morning; this phase shift is considered to be fundamental for circadian clock function. In sharp contrast, in the naked mole‐rat both Per1 and Per2, as well as Bmal1, peaked at the same time in the morning—around ZT2—suggesting the organization of the molecular circadian oscillator was different. Moreover, gene expression rhythms associated with glucose metabolism and mTOR signaling also differed between the species. Although the activity of mTORC1 was lower, while that of mTORC2 was higher in naked mole‐rat livers compared to mice, unlike that of mice where the expression profiles of glucose metabolism genes were not synchronized, these were highly synchronized in naked mole‐rats and likely linked to their use of feeding times at zeitgebers.